Silver nanowires as receiving-radiating nanoantennas in plasmon-enhanced up-conversion processes. Issue 4 (15th December 2014) - Piatkowski, D.; Hartmann, N.; Macabelli, T.; Nyk, M.; Mackowski, S.; Hartschuh, A.
Abstract : Silver nanowires coupled with upconverting nanocrystals enhance absorption/emission rates, introduce polarization sensitivity and guide fluorescence energy in plasmonic system. Abstract : We demonstrate efficient coupling between plasmons in a single silver nanowire and nanocrystals doped with rare earth ions, α-NaYF4 :Er 3+ /Yb 3+ . Plasmonic interaction results in a sevenfold increase of the up-converted emission of nanocrystals located in the vicinity of the nanowires as well as much faster luminescence decays. The enhancement of the emission can be precisely controlled by the polarization of the excitation laser and is significantly stronger for polarization parallel to the nanowire antennas. Imaging of angular-resolved emission patterns in the Fourier plane reveals plasmon-mediated luminescence, where the up-converted radiation is emitted via the nanowire antennas as leakage radiation.